HUBUNGAN POLA ASUH PERSUASIF DAN MOTIVASI BELAJAR TERHADAP KEDISIPLINAN SISWA KELAS VII MTS NGAWEN - Maesaroh Mardani (Jurnal Pendidikan Agama Islam, 2013)
This research is a field with a quantitative approach to the study of students taking the subject MTsN Ngawen Gunungkidul. The purpose of this study was to measure the extent of persuasive parenting parents applied at home, a large degree of motivation to learn the creed of morals, discipline and level of learning. Furthermore ini juga research aims to describe how much influence the motivation to learn the creed and morals of the discipline of data is done by holding belajar. The data collection was done through observation, interviews, documentation and questionnaires.The results showed that: 1) The level of parental persuasive parenting class VII MTsN Ngawen Gunungkidul in middle category, the motivation to learn faith and morals in the high category, and discipline learned in the high category. This suggests that if the low persuasive parenting learning motivation and discipline students will learn tinggi. 2) Parenting persuasive parent class VII MTs Ngawen Gungngkidul not have a significant relationship terhadap learn discipline because sig 0.78 ≥ 0:05. This suggests that the busyness of parents outside the home can not help improve learning discipline siswa. 3) learning motivation and moral theology class VII MTs Ngawen said to have a positive and significant relationship to the class VII student learning discipline MTsN Ngawen Gunungkidul is at the 0,000 sig ≤ 0.05, which means the higher the motivation to learn in students studying theology and morals, especially the higher level of discipline to learn siswa. 4puls) Major contribution faith - moral motivation to learn discipline learned at 44.4 % and the remainder is 55, 6 % is influenced by other factors.